IMPLEMENTASI KEWENANGAN KEJAKSAAN SEBAGAI PEMOHON DALAM MENGAJUKAN KEPAILITAN DEMI KEPENTINGAN UMUM BERBASIS NILAI KEADILAN SOSIAL (JURNAL HUKUM SEHASEN, 2019)
The Public Prosecutor's Office may act in and out of court for and on behalf of the state or government. Subject to the provisions of Article 2 paragraph (2) of Law Number. 37 Year 2004 jo Government Regulation Number. 17 Year 2000 stipulates that the Attorney General as one of the parties who may file for bankruptcy, with the requirements to be met is that no other party has submitted similar applications in the public interest. Based on the matters in this journal then formulated in the formulation of the problem namely; How is the implementation of the authority of the Prosecutor Office as an applicant in filing for bankruptcy in the public interest based on the value of social justice? What factors influenced the effectiveness of the implementation of the authority of the Prosecutor as an applicant in filing for bankruptcy in the public interest?Sociolegal approach method with postpositivist paradigm according to Norman K Denzin and Yvona S Lincoln. Where the authors analyzed from the angle of ontology, epistemolginya and metodelogi. From the results of the discussion in this paper shows that the implementation of the authority of the Prosecutor Office as an applicant in bankruptcy in the public interest based on the value of social justice, regulated in the rules of applicable laws. And the effectiveness of the implementation of Authority to the Attorney as Petitioner In Filing Bankruptcy Case for Public Interest requires the performance of the Prosecutor in establishing the national legal system. Because basically the Prosecutor is one part of the legal structure that affects the workings of the law. Keywords: Authority of Attorney, Applicant of Bankruptcy, Value of Social Justice